Influence of Setting Accelerator Dosage on Fresh Properties, Strength Development and Microstructure of Ultrafine Silicate Cement Grout - Zhou, Bofang; Meng, Xiangrui; Wang, Yanfen (International Journal of Materials Science and Technology Studies, 2026)
As mining depth increases, roadway surrounding rock in underground coal mines is increasingly prone to severe deformation and failure. In particular, the mechanical behaviour of weak, soft rock masses is highly heterogeneous and difficult to control, making reliable stability management challenging. Grouting reinforcement has therefore become an effective intervention for improving the integrity and load-bearing capacity of the surrounding rock. With the growing complexity of engineering–geological conditions, grouting materials are required to deliver rapid setting and early strength while maintaining anti-dispersion performance and long-term durability. To meet the demand for fast solidification and efficient support under deep-mine conditions, this study develops an ultrafine silicate cement–based grout incorporating an expansive agent (8%), a water-reducing agent (0.35%) and a setting accelerator (1.0–3.5%), with the water-to-cement ratio fixed at 0.40. Using a suite of macro- and micro-scale characterization methods, we quantify how accelerator dosage governs slurry workability, mechanical performance and the microstructure of hardened grout, and we elucidate the associated hydration mechanisms. Increasing accelerator content markedly shortened the setting time by 61.54–97.50% (relative to the control) but reduced flowability, whereas both compressive and flexural strengths exhibited a non-monotonic trend, increasing initially and then declining at higher dosages. An accelerator dosage of 2.5% yielded the best overall performance, increasing 3-day compressive and flexural strengths by 14.40% and 125.12%, respectively, and improving 28-day compressive strength by 14.76%. Microstructural evidence further indicates that an appropriate accelerator dosage promotes a denser and more homogeneous hydration-product network, thereby enhancing structural stability. Overall, maintaining the accelerator dosage within 2.0–2.5% provides an optimal balance between setting kinetics and mechanical capacity, and is therefore well suited for grouting applications in high-stress deep-coal environments.